The application and interpretation of principles of corporate governance in the state owned entities (ESKOM) in South Africa - Ramatabana, Tshepo Milford (My University, 2017)
Good corporate governance is essentially about effective, responsible leadership. This is characterized by the ethical values of responsibility, accountability, fairness and transparency, which values underpin good corporate governance. After the promulgation of the Kings Code, amendment of the Companies Act and the promulgation of the Public Financial Management Act, it has been shown that most of the leadership and board of directors in state owned entities have not been following the guidelines and principles provided in these legislations and that’s why most of them are in disarray. It is, therefore, the objective of this research to help restore the integrity and confidence in state owned entities and the need to a draw the line between personal interest and that of the company. An appropriate approach will be to conduct training or a workshop, whereby appointed persons can be reminded of how to discharge their rights and duties before they are instated into a particular post.
Thesis (LLM.) -- University of Limpopo, 2017.
Keywords: Corporate governance; State-owned entities; Government business enterprises; Corporate governance -- Law and legislation